UPAYA GURU DALAM PENINGKATAN KETERAMPILAN MOTORIK HALUS MELALUI KEGIATAN MELIPAT KERTAS PADA ANAK USIA DINI DI RA SYARQUL AUSAT GUNUNGHALU - HANIAH, NENG (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
In this study, researchers chose a place of research in a Raudhatul Athfal (RA) institution in the Gununghalu sub-district of West Bandung Regency, namely in RA Syarqul Ausat Gununghalu. In this institution researchers still find common problems of early childhood education that can occur in educational institutions anywhere. The general problem is in the form of fine motor skills that are still difficult to apply to early childhood educators. That is why they are not enthusiastic about developing fine motor skills. One of the learning activities that can improve fine motor skills is folding paper. This study uses a descriptive research method with a qualitative approach. In this case the researcher only explains or describes a situation or fact in the field without the need to analyze the interrelationship between variables. The stages in this study include several steps, namely the planning stage, implementation phase, and evaluation stage. Based on the results of the previous analysis and discussion, the researcher can conclude that the teacher in an effort to improve Fine Motor Skills Through the Activity of Folding Paper in Early Childhood in RA Syarqul Ausat Gununhalu is good. This can be seen from the acquisition of the number of acquisition scores from the results of the evaluation of early childhood as many as 1247 with an average number of 83 classified as good